Design and characterisation of a 200 GHz tunable lens‐coupled annular‐slot antenna with a 50 GHz tuning range. Issue 11 (1st August 2014) - Jiang, Zhenguo; Rahman, Syed M.; Hesler, Jeffrey L.; Fay, Patrick; Liu, Lei
Abstract : A frequency‐tunable lens‐coupled annular‐slot antenna (ASA) with a nearly 50 GHz tuning range has been designed, fabricated and characterised at the G‐band (140–220 GHz). Initial numerical electromagnetic simulation results show that the resonant frequency of the antenna can be tuned effectively, with a tunability of ∼2.5 GHz/fF associated with the capacitive loading from the varactor. In addition, simulated far‐field antenna patterns have demonstrated that the addition of the varactor used to implement the capacitive loading does not strongly affect the antenna's radiation properties. This design has been demonstrated experimentally, using a Schottky varactor diode with a zero‐bias junction capacitance of ∼16 fF mounted on a 200 GHz ASA fabricated on a semi‐insulating silicon wafer. Measurement at G‐band shows a frequency tuning range of nearly 50 GHz by varying the voltage bias of the Schottky varactor diode from −5 to 1 V. The measurement results agree well with simulations based on an equivalent circuit model for the Schottky diode and the antenna. Measured far‐field radiation patterns of the lens‐coupled tunable ASA at 203 GHz show good agreement with calculations based on the ray‐tracing technique, verifying that the diode mounting does not affect the antenna radiation properties significantly. This type of tunable ASA is very promising for realising reconfigurable detectors and focal‐plane arrays at terahertz (THz) frequencies, and may find applications in future adaptive submillimetre‐wave/THz communication systems.